Poly lactic-co-glycolic acid-based nanoparticles as delivery systems for enhanced cancer immunotherapy - Gao, Lei; Li, Jing; Song, Tianhang (Frontiers in Chemistry, 2022)
Cancer has emerged as one of the most severe diseases in modern times, various therapies have advanced remarkably in recent decades. Unlike the direct therapeutic targeting tumor cells, immunotherapy is a promising strategy that stimulate the immune system. In cancer immunotherapy, polymeric-based nanoparticles can serve as deliver systems for antigens and immunostimulatory molecules, and they have attracted increasing attention and revolutionized cancer therapy. Poly (lactic-co-glycolic acid) (PLGA) is the most frequently used clinically approved biodegradable polymer and has a broad scope of modification of its inherent properties. Recent advances in PLGA based drug delivery systems in cancer immunotherapy have been described in this mini review, with special emphasis on cancer vaccines and tumor microenvironment modulation.